The Elasticity of Taxable Income in New Zealand - Iris Claus; John Creedy; Josh Teng (New Zealand Government, The Treasury, 2012)
This paper reports estimates of the elasticity of taxable income with respect to the net-of-tax rate for New Zealand taxpayers. The relative stability of the New Zealand personal income tax system, in terms of marginal rates, thresholds and the tax base, provides helpful conditions for deriving these estimates. The elasticity of taxable income was estimated to be substantially higher for the highest income groups. Generally it was higher for men than for women. Changes in the timing of income flows for the higher income recipients were found to be an important response to the announcement of a new higher-rate bracket. The marginal welfare costs of personal income taxation were consistent across years, being relatively small for all but the higher tax brackets. For the top marginal rate bracket of 39 per cent, the welfare cost of raising an extra dollar of tax revenue was estimated to be well in excess of a dollar. Furthermore, for the top bracket the marginal tax rate was often found to exceed the revenue-maximising tax rate.
Keywords: H24; H31; 330; Income taxation; Taxable income; Elasticity of taxable income; Excess burden of taxation.; Einkommensteuer; Besteuerungsverfahren; Einkommensverteilung; Elastizität; Excess Burden; Theorie; Neuseeland